The need for information literacy education an assessment of the information literacy competency of College of Engineering freshmen students at the University of the Philippines Diliman - Ramos, Jeremy C.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Information literacy (IL) is a set of skills used by any learner to locate, evaluate, and properly use obtained information. Its recently development in the Philippines necessitates for more investigations to be conducted to build a better foundation for all learners to enhance the way they utilize information.
This study aimed to assess the level of competency of UP College of Engineering undergraduate freshmen students in terms of information literacy. The study sought to examine if factors such as gender, age, socio-economic background, the kind of secondary school the respondent graduated from, their current course under Engineering and any library training are significant in affecting their performance in the competency assessment.
Students were made to answer a twenty-six item questionnaire measuring Information Literacy Competency Standards 1 and 2 of the ACRL. The data was then analyzed via One-Way ANOVA, frequency distribution and percentage studies, as well as post-hoc tests and Pearson's.
Tests yielded higher scores for female over the males. Furthermore, respondents who belonged to higher socio-economic divisions scored higher than their counterparts from lower divisions, and those who graduated from private schools performed better than students who came from public or science high schools. By contrast, respondents from different age groups had no significant differences in their scores. Attendance in library orientations or workshops also did not prove to be an influencing factor in the study.
Due to the students' low passing rate (40) over the test, as well as many weaknesses in both standards, further improvements must be made regarding development of university students' skills in information location, retrieval, evaluation and use.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- College of Engineering -- Freshmen; Information literacy -- Philippines -- Quezon City